Civil Society and World Regions: How Citizens Are Reshaping Regional Governance in Times of Crisis - Fioramonti, Lorenzo (Lexington Books, 2013)
Supranational regionalism and regional integration have for a long time been top-down processes, led by the few and imposed on the many. The role of citizens, especially those active in civil society, has been neglected by scholars, students, and commentators of regionalism. In reaction to the prevalence of these top-down models, a “new regionalism” approach has proliferated in the past few years. This book aims to further develop such a research agenda by providing an up-to-date overview of the contribution of civil society to world regionalism, from Europe to Africa, Asia, and the Americas. This is not only relevant as a research topic; it is also of critical importance from a political standpoint. As regions across the world experience prolonged governance crises, it becomes paramount to understand the extent to which these new regional formations actually reflect the interests and needs of their people. While old regionalism was accepted as a de facto elite-driven byproduct of both the Cold War and neoliberal globalization, the twenty-first-century regionalism—if it is to survive—will need to refocus its objectives through new forms of participation and inclusion. Regions without citizens are unlikely to stand the test of time, especially in times of crises.